1996
DOI: 10.1007/bf01411122
|View full text |Cite
|
Sign up to set email alerts
|

A flexible metal ventricular catheter for treatment of complicated and protracted infections of the cerebrospinal fluid spaces: Preliminary experiences

Abstract: In the management of shunt infection, the use of ventricular catheters made of silicone rubber for the temporary external drainage of cerebrospinal fluid (CSF) is general practice. However, the eradication of the primary source of infection may be hindered by the affinity of bacteria to silicone-based material. Compared to silicone catheters, a metal drainage device for temporary ventriculostomy appears to offer more favourable conditions for successful eradication of the infection. Since metal needles cannot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…An additional review of the initially identified articles was performed for suitability, and resulted in exclusion of articles that included patients on anticoagulants, use of alternative techniques or techniques that do not reflect current procedures, or studies that reported hemorrhage as a result of underlying pathology rather than directly due to ventriculostomy (e.g., aneurysmal rebleed after ventriculostomy) [14][15][16].…”
Section: Search Strategymentioning
confidence: 99%
“…An additional review of the initially identified articles was performed for suitability, and resulted in exclusion of articles that included patients on anticoagulants, use of alternative techniques or techniques that do not reflect current procedures, or studies that reported hemorrhage as a result of underlying pathology rather than directly due to ventriculostomy (e.g., aneurysmal rebleed after ventriculostomy) [14][15][16].…”
Section: Search Strategymentioning
confidence: 99%
“…5,[8][9][10] Infectious agents have included a large spectrum of organisms including even Candida. 11,12,20 Several recent articles have described various techniques to decrease the rate of infectious complications, such as flexible metal ventriculostomies 13,14 or longtunnel ventriculostomies, which require a separate procedure. 15 Others have recommended placement of the EVD in the operating room (OR).…”
Section: Introductionmentioning
confidence: 99%
“…Catheter-associated infection of the cerebrospinal fluid (CSF) is a well-known and eventually devastating complication of external ventricular drainage (EVD) (2,13). The infection rate can be as high as 30% and increases three-fold more than 18 days after implantation of conventional (silicon) catheters (23,25). Even though it is standard practice to administer antibiotics prophylactically (15), the CSF infection cannot be totally excluded (13,25).…”
Section: Introductionmentioning
confidence: 99%
“…In order to minimize the risk of ventriculitis several approaches have been proposed both for adults (9,13,17,21) and children (20,22,24,25); percutaneous needle puncture (25), 'Duisburger Nadel' (10), endoscopic third ventriculostomy alone or combined with choroid plexus (24), antibiotic-impregnated catheters (AIC) (17,21,22), nanoparticles (silver)-impregnated catheters (9,13) and flexible metal ventricular catheters (23) represent only some of the current practices. In the case of verified ventriculitis the choice of the appropriate catheter to use is far more troublesome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation